CHINGIZ AITMATOV – WRITER OF THE EURASIAN SPACE - М. О. Холбоева (Web of Journals Publishing, 2024)
The article is devoted to the work of Chingiz Aitmatov in the context of Eurasian culture. The main milestones in the work of the famous writer and his role in the modern Eurasian space are considered. Emphasis is placed on the philosophical comprehension of Ch. Aitmatov's work within the framework of spiritual and moral traditions and national customs of the Turkic peoples, which had a special impact on the entire Eurasian ethnos.
Keywords: culture; Eurasia; Kyrgyzstan; literary works; anthropological factor; Genghis Khan; post-Soviet space.